Kansas rural adolescent health issues and needs: focus groups with 65 adolescents across four counties - Miller, Bryant S. (Kansas State University, 2016)
This qualitative study explored 65 rural adolescents' perceptions of health issues and needs. Focus groups were conducted with adolescents in six rural communities in Kansas. Analysis of transcripts suggested that the adolescents’ face numerous health issues that strongly influence their behaviors and expressed need for assistance. Adolescent health issues stemmed across biological, psychological, and social factors. Major themes evolved around challenges pertaining to healthy choices in food and nutrition, physical activity, stress management, sexual health, perceptions of invincibility, and poor role-modeling. To improve well-being adolescents need privacy, effective conversations, accessible health services, reliable education, and prioritization of healthy lifestyles. Implications for clinical and research are discussed.
Keywords: Adolescents; Qualitative research; Rural communities; Biopsychosocial model